1989
DOI: 10.1242/dev.105.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of tissue inhibitor of metalloproteinase (TIMP) RNA

Abstract: Single-stranded antisense RNA probes have been used to study the expression of the metalloproteinase inhibitor TIMP (tissue inhibitor of metalloproteinases), during mouse embryogenesis and in adult tissues. Using a sensitive RNase protection assay, low levels of transcript can be detected in a variety of tissues, including maternal deciduum, embryonic kidney, lung and amnion. Higher levels are seen in osteogenic tissues such as calvaria, while the highest level in any tissue is found in the ovary, though even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to its inhibitory effect on MMPs, TIMP1 participates in multiple processes such as cell proliferation, cell survival and differentiation, and apoptosis [ 5 , 6 ]. Over the last three decades, studies have demonstrated that TIMP1 is a ubiquitous protein expressed in widespread mammalian tissues, remarkably in the reproductive organs [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In goats, TIMP1 was detected in the oocytes, cumulus, granulosa, and theca cells of antral follicles and corpus luteum [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its inhibitory effect on MMPs, TIMP1 participates in multiple processes such as cell proliferation, cell survival and differentiation, and apoptosis [ 5 , 6 ]. Over the last three decades, studies have demonstrated that TIMP1 is a ubiquitous protein expressed in widespread mammalian tissues, remarkably in the reproductive organs [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In goats, TIMP1 was detected in the oocytes, cumulus, granulosa, and theca cells of antral follicles and corpus luteum [ 14 ].…”
Section: Introductionmentioning
confidence: 99%